DIGITAL TRANSFORMATION OF THE FINANCIAL SECTOR OF THE WORLD ECONOMY: TRENDS AND RISKS - Baula, O.V.; Liutak О.М. (The actual problems of regional economy development, 2022)
The aim of the article is to solve the scientific problem of identifying patterns of digital transformation of the financial sector of the world economy, systematization of factors and risks of this process, as well as substantiation of practical recommendations for their leveling. To achieve the goal of the study used a set of general and special research methods: systematization and generalization, analysis, induction, scientific abstraction and explication, methods of descriptive statistics and visual analysis. The overall global investment activity in fintechs was monitored, namely: the dynamics of direct and venture investments, as well as M&A agreements (cross-border mergers and acquisitions) for 2018-2021 were assessed. cross-border mergers and acquisitions; direct investment in fintech is relatively insignificant; in 2021 record for the studied period were venture investments in fintech; Virtually all fintech sectors are characterized by dynamic growth, among which the leaders are the blockchain subsector, cryptocurrency, welfare management technologies, and cybersecurity. The article considers the factors of global spread of fintech and their digital transformation: declining confidence in traditional financial instruments and products, intensifying the spread of digitalization processes worldwide and industry and the objective advantage of using to meet the needs of entities, expanding Internet space and development mobile devices, popularization of social networks and messengers, global trends to increase the desire for innovation, the formation of dependencies on automated technologies. The risks of digital transformation of the financial sector of the world economy according to the Financial Stability Board, the Bank for International Settlements, and the International Economic Forum are considered. Among which the risk of cyber attacks in the financial sector is one of the most dangerous. Measures to reduce the risks of digital transformation of the financial sector of the world economy are outlined. In order to minimize the risks caused by the need to spread digital transformations in the fintech sector, it is advisable to ensure the creation of a regulatory framework governing customer relations through remote channels, and the activities of fintech companies. World experience shows that the ability to actively interact with technology companies in the development and implementation of innovative solutions, outsourcing of innovations or other forms of cooperation is an important factor in successful digitalization. It is also reasonable to develop a comprehensive digital strategy, both at the macro level and for each individual institutional participant in the financial sector. The results of the study can be useful for the development of scientifically sound recommendations for preventing the risks of digital transformation of the fintech sector.